A review of pediatric femoral fracture patterns, surgical managements, and outcomes - Almigdad, Ahmad K.; Banimelhem, Khalid A.; Almanasir, Ghandi K.; Altaani, Ehab M.; Al-Qudah, Ala K. (International Journal of Research in Orthopaedics, 2021)
Background: Femoral fractures are the most common pediatric orthopedic fractures that require hospitalization. The non-accidental injury should be suspected in early infancy and non-ambulatory children. Treatment of pediatric femoral fractures is widely variable and depends on intrinsic and extrinsic factors. This study presents pediatric femoral fracture epidemiology and outcomes and reviews the literature regarding best practices in pediatric femoral fractures. Methods: This retrospective study reviewed the clinical and radiological records of forty-sevens femur fractures in the pediatric age group from September 2020 until June 2021 in Prince Rashid bin AL Hassan Military Hospital in Jordan. Results: Males form 80.9% of patients. The mean age for the patients was equal to 6.70 years (±3.91). Falling is responsible for the majority of the injury. The middle femur shaft was fractured in 46.8%, and the pathological fracture was found in 17% of patients. Non-operative treatment by cast represents 42.6%. All fractures were healed at 7.90 weeks (±2.37). Conclusions: Pediatric femur fracture lacks standardized treatment. Nevertheless, most fractures healed with satisfactory results. Younger age groups are more likely to be treated non-operatively. Non-surgical treatment is more prone to shortening, angulation, and later return to weight-bearing and activity. Children older than eight years treated by plating demonstrated faster healing, return to full weight-bearing, and lower complication rate.